ANALYSIS OF PARKING CHARACTERISTICS AND THE EFFECT OF ON STREET PARKING ON TRAFFIC PERFORMANCE - Zulvia, Avita; Rizani, Mohammad Debby; Suwandi, Putri Anggi Permata (International Journal of Sustainable Building, Infrastructure and Environment (IJOSBIE), 2022)
The space are available for park vehicle on the edge road in the area center city and along main street thing to do with permanent there is restrictions and controls as well as Settings or often called on street parking(Clarkson Grg Lesby and Bary Hicks, 1988). Study this background behind by trouble performance then traffic that is less than optimal is caused by the presence of on street parking on lane bicycle on Kartini Street, Salatiga City. In resolve problem the required existence analysis about characteristics parking and influence on-street parking along Kartini Street, Salatiga City. Method used in study this that is method approach descriptive quantitative. Collecting the data obtained from results interview, notes field, documentation private, notes researchers, and documents residents other. Study this show that characteristics parking and influence on-street parking to performance then traffic on Kartini Street, Salatiga City for duration parking belong to Category 1 and significant high turnover duration short, in general vehicle parking not enough from one hour with duration parking short in general for parking in the center spending, with capacity street 2489,22 pcu/hour, speed current free 37,665 km/hour vehicles as well as level service belong to category Level Of Service (LOS) B (0.20-0.44) with characteristics current stable, speed a little limited by past traffic, driver still could free in choose the speed.Â